Wild edible mushrooms of Khumbu Region, Nepal - Giri, Anjana; Rana, Prabina; Shrestha, Sanjib Kumar (Journal of Natural History Museum, 2008)
The study was conducted in Sagarmatha National Park and its buffer zone in Solu-Khumbu region (2500-4000m) during the year 2004. A total of 150 species of mushrooms were collected, among these 23 species were identified as wild edible mushrooms with the help of local people. About 6 species of mushroom comprising Russula metachroa Hongo, Tylopilus eximus (Peck) Singh, and Naematoloma capnoides (Fr.) Karst and 3 spp. of Boletus are considered as new addition to the edible mushroom list of Nepal. The diversity of wild edible mushrooms were found high in Khumjung (3800m) and low in Pangboche (4000m). The majority of wild edible mushrooms belong to the family Boletaceae, Amanitaceae, Tricholomataceae, etc. J. Nat. Hist. Mus. Vol.22, 2005 p.148-156